Empowering Leadership and Turnover Intention in Corporate Organizations: A Meta Analytical Perspective (2022-2024) - Angelita, Evelyn Andriana; Soeling, Pantius Drahen (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
In an era of increasingly fierce competition, leaders in corporate organizations are required to empower their employees to be more effective and efficient. Leader empowerment can increase employee autonomy, motivation, and job satisfaction, which ultimately affects turnover intention. This study aims to analyze the impact of leader empowerment on turnover intention in corporate organizations through a meta-analysis approach of five related articles. The method used in this research is meta-analysis, which collects, analyzes, and synthesizes the results of various empirical studies on leadership empowerment and turnover intention. Relevant literature was selected based on certain criteria to ensure the validity and relevance of the data. The results show that leadership empowerment has a positive and negative influence on turnover intention. On the one hand, leadership empowerment can reduce turnover intention by increasing employee motivation and engagement. On the other hand, increasing employees' capabilities may encourage them to seek opportunities in other companies. This finding emphasizes the importance of leaders in understanding the behaviours and expectations of their subordinates and their involvement in decision-making. Overall, leadershipempowerment plays an important role in turnover intention in organizations. To minimize turnover intention, leaders need to implement strategies that empower employees while considering the complexity of diverse organizational contexts. This effort is expected to create a more stable and productive work environment.